Cancer survivorship: understanding the patients' journey and perspectives on post-treatment needs - Conor Hussey; Moira Hanbridge; Maura Dowling; Ananya Gupta (BMC, 2024)
Abstract Background Cancer treatments have many adverse effects on patient's health leading to poor cardiorespiratory capacity, muscular- degeneration, fatigue, loss of strength and physical function, altered body-composition, compromised immune-function, peripheral neuropathy, and reduced quality of life (QOL). Exercise programs can significantly increase functional capacity when tailored to individual needs, thus improving health. Exercise interventions in cancer rehabilitation, when supported by appropriate nutrition can be effective in attaining a healthy weight and body-composition. The successful rehabilitation program should also include psycho-social education aimed to reduce anxiety and improve motivation. Methods The current study aimed to collect information on the post-treatment needs of cancer patients including barriers and expectations facing them, their caregivers and their families through consultation in focus group interviews. Cancer survivors living in the Republic of Ireland were recruited from the University Hospital Galway, community-based cancer centres, cancer support groups and social media platforms to participate in the study and attend a focus group interview. The focus group discussions were designed to obtain information on the collective views of cancer survivors on relevant topics selected. The topics were developed in consultation with a patient and public involvement (PPI) group supporting the study. The topics list was circulated to all participants prior to the focus group. The interviews were audio recorded and transcribed verbatim. Focus group transcripts were analysed subjected to a thematic framework analysis using NVivo. Results Thirty-six participants took part in 9 focus groups. Our analysis uncovered two main themes. The first theme 'cast adrift with no direction' was grouped into three sub-themes: everything revolves around treatment; panic and fear; and what exercise should I be doing? The second theme 'everybody is different' was clustered into two sub-themes: side effects get in the way; and personalised exercise program. Conclusion The study highlighted the lack of information and support needed by patients living with and beyond cancer. The study also highlighted the need for a personalised exercise programme designed to target the individual patient symptoms that would be ideal for the mitigation of long term symptoms and in improving QOL.